IMPLEMENTATION OF PANCASILA CHARACTER EDUCATION IN HOMBO BATU IN SOUTH NIAS - Harefa, Darmawan (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to analyze the implementation of Pancasila character education through Hombo Batu activities in South Nias. Hombo Batu, a traditional game that embodies local wisdom values, is considered an effective tool for developing students' character in alignment with the principles of Pancasila, such as discipline, cooperation, and responsibility. This research employs a qualitative approach with a case study method conducted in several elementary schools in South Nias. Data were collected through observations, interviews with teachers and students, and relevant document studies. The findings indicate that the application of Hombo Batu in character education can strengthen the values of Pancasila, particularly in the development of mutual cooperation, discipline, and responsibility among students. However, several challenges, such as limited facilities and time constraints, hinder the optimal implementation of this activity. The study suggests that improving supporting facilities and providing teacher training are necessary to enrich the implementation of character education based on local wisdom in South Nias schools